1998
DOI: 10.1126/science.280.5363.564
|View full text |Cite
|
Sign up to set email alerts
|

The Lost Colony and Jamestown Droughts

Abstract: Tree-ring data from Virginia indicate that the Lost Colony of Roanoke Island disappeared during the most extreme drought in 800 years (1587-1589) and that the alarming mortality and the near abandonment of Jamestown Colony occurred during the driest 7-year episode in 770 years (1606-1612). These extraordinary droughts can now be implicated in the fate of the Lost Colony and in the appalling death rate during the early occupations at Jamestown, the first permanent English settlement in America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
110
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 196 publications
(116 citation statements)
references
References 3 publications
6
110
0
Order By: Relevance
“…The majority of these tree-ring studies have focused on the central and western USA because an abundance of suitable tree-ring data exists and the relationship between tree rings and climate is quite direct. At least 2 recent studies have focused on reconstructing growing-season moisture conditions in the eastern USA (Stahle et al 1998, Druckenbrod et al 2003. Stahle et al (1998) reconstructed the growing-season moisture conditions for the Tidewater region of Virginia and North Carolina from A.D. 1185 to 1984.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of these tree-ring studies have focused on the central and western USA because an abundance of suitable tree-ring data exists and the relationship between tree rings and climate is quite direct. At least 2 recent studies have focused on reconstructing growing-season moisture conditions in the eastern USA (Stahle et al 1998, Druckenbrod et al 2003. Stahle et al (1998) reconstructed the growing-season moisture conditions for the Tidewater region of Virginia and North Carolina from A.D. 1185 to 1984.…”
Section: Introductionmentioning
confidence: 99%
“…At least 2 recent studies have focused on reconstructing growing-season moisture conditions in the eastern USA (Stahle et al 1998, Druckenbrod et al 2003. Stahle et al (1998) reconstructed the growing-season moisture conditions for the Tidewater region of Virginia and North Carolina from A.D. 1185 to 1984. They found that this region has experienced substantial inter-annual and decadal variability in growingseason moisture conditions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations